PROGRAM APRESIASI BAGI PEMERINTAH DAERAH (PEMDA) DALAM MELAKSANAKAN TATA KELOLA (GOOD GOVERNANCE) GUNA MEMAJUKAN KEPARIWISATAAN DI DAERAH - Ismayanti Ismayanti; Titin Astuti; Ina Djamhur; Sutyastie Soemitro Remi (Faculty of Economic and Business, 2014)
The success of region is largely determined by the commitment of the local government in the development of tourism. Good governance will certainly provide prosperity for the community. This first year multi-disciplinary research has a purpose: to design blueprint appreciation program for local governments that are committed in developing regions of Tourism through good governance and delivering award of appreciation to the government. This study examines several aspects of appreciation through commitment identification and governance survey using analytical methods of AHP. Tourism appreciation blueprint is implemented with program testing. The results achieved is the publication and implementation of the blueprint of appreciation in cooperation with the Eljohn Publishing through Travel Club Tourism Award 2012 from the magazine Travel Club. The results is 40 nominees from the provincial governments, district and city governments. From the nominees, it is determined the winner of the provincial government consisting of 3 province, 9 city and 13 district government. Positive implications occurs after administration of appreciation and local prideness increases when each winner received awars and regional leaders gave speech in front of live audience and broadcasting live all over Indonesia. Besides these, dignity of each government showed in local and national publications in the electronic media and print media. Of these positive implications, it is recommended to conduct a similar program on a regular basis and measured the impact of the annual tribute to the development of tourism in the area so that the program becomes one measure the progress of regional tourismDOI: 10.15408/ess.v4i1.1962